PERGESERAN IDEOLOGI MAHASISWA MUSLIM DI UNIVERSITAS MUHAMMADIYAH KENDARI - Muhammad Dachlan (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
University students are young figures who are responsible as the nation successors thus they should have the vision and mission of nationality. However, this ideal condition can apparently not found in all universities. For example, the movement of the student organization at Muhammadiyah University Kendari was proven as not having the vision and mission of nationality. This study employed qualitative methods to describe the student organization at the University of Muhammadiyah Kendari. The findings reveal that: firstly, the university banned the growth and development of religious organizations other than IMM. Secondly, despite the university ban, student organization such as Gema Pembebasan (i.e. the development of HTI) kept appearing. Student religious movement on one hand is an encouraging phenomenon in the Islamic dawah and education. However, when it is not supervised with the concept of nationalism, the student organization of this kind will lead to radical movements in religious organizations.